PENGARUH MODEL DISCOVERY LEARNING BERBANTU E-LKPD INTERAKTIF MICROSOFT SWAY TERHADAP PENINGKATAN HOTS PESERTA DIDIK SEKOLAH DASAR - Khairani, Fadhilah; Surahman, Maman; Destini, Frida; Utaminingtias, Ika Wulandari (STKIP Persada Khatulistiwa Sintang, 2024)
The background of this research is that students' HOTS is still far from expectations and educators do not yet understand discovery learning assisted by Microsoft Sway's interactive e-LKPD. The aim of the research is to determine the effect of discovery learning assisted by Microsoft Sway's interactive e-LKPD on thematic learning and to test the effectiveness of discovery learning assisted by Microsoft Sway's interactive e-LKPD on students' HOTS. This research is experimental research. The research method applied a quasi experimental design. The research design used was a non-equivalent control group design. The research population consisted of 53 students. The research sample was 26 students of class VB as the experimental group and 27 students of class VA as the control group. The data collection technique are tests, the test instrument is in the form of multiple choice questions. The test data was analyzed using simple linear regression by using SPSS 26. The results showed that the Sig. amounting to 0.003<0.05. It can be concluded that the implementation of discovery learning model assisted by Microsoft sway’s interactive e-LKPD has a significant effect in increasing students' HOTS.